2015
DOI: 10.1097/ede.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

Miscarriage Among Flight Attendants

Abstract: Background Cosmic radiation and circadian disruption are potential reproductive hazards for flight attendants. Methods Flight attendants from 3 US airlines in 3 cities were interviewed for pregnancy histories and lifestyle, medical, and occupational covariates. We assessed cosmic radiation and circadian disruption from company records of 2 million individual flights. Using Cox regression models, we compared respondents (1) by levels of flight exposures and (2) to teachers from the same cities, to evaluate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 26 publications
5
38
0
1
Order By: Relevance
“…Of note, frequency of intercourse was not measured [44]. A study of more than 2000 female flight attendants revealed a significantly increased risk of first trimester miscarriage when work times coincided with the sleep period based on time zone of origin [45].…”
Section: -163)mentioning
confidence: 99%
“…Of note, frequency of intercourse was not measured [44]. A study of more than 2000 female flight attendants revealed a significantly increased risk of first trimester miscarriage when work times coincided with the sleep period based on time zone of origin [45].…”
Section: -163)mentioning
confidence: 99%
“…Adverse reproductive outcomes have been suggested in some studies of female flight attendants [ Aspholm et al , ; Lauria et al , ; Waters et al , ]. Also, a 70% increase in the risk of miscarriage among flight attendants, who received a dose of 0.1 mGy (1 Gy = J/kg) or more in the first trimester, was shown in a recent epidemiological study [ Grajewski et al , ].…”
Section: Introductionmentioning
confidence: 97%
“…We used data from a retrospective cohort study of reproductive health among female flight attendants, the original aim of which was to estimate cosmic ionizing radiation and circadian disruption exposures among flight attendants and their potential association with adverse reproductive health outcomes such as miscarriage and menstrual function (12). Female flight attendants aged 18–45 years were selected from employee lists from three US commercial airline hubs in Detroit, Miami, and Seattle.…”
Section: Methodsmentioning
confidence: 99%